Differences in Short‐ and Long‐Term Mortality Associated With BMI Following Coronary Revascularization. Issue 4 (April 2017) - Terada, Tasuku; Forhan, Mary; Norris, Colleen M.; Qiu, Weiyu; Padwal, Raj; Sharma, Arya M.; Nagendran, Jayan; Johnson, Jeffrey A.
Abstract : Background: The association between obesity and mortality risks following coronary revascularization is not clear. We examined the associations of BMI (kg/m 2 ) with short‐, intermediate‐, and long‐term mortality following coronary artery bypass graft surgery (CABG) and percutaneous coronary intervention (PCI) in patients with different coronary anatomy risks and diabetes mellitus status. Methods and Results: Data from the Alberta Provincial Project for Outcomes Assessment in Coronary Heart Disease (APPROACH) registry were analyzed. Using normal BMI (18.5–24.9) as a reference, multivariable‐adjusted hazard ratios for all‐cause mortality within 6 months, 1 year, 5 years, and 10 years were individually calculated for CABG and PCI with 4 prespecified BMI categories: overweight (25.0–29.9), obese class I (30.0–34.9), obese class II (35.0–39.9), and obese class III (≥40.0). The analyses were repeated after stratifying for coronary risks and diabetes mellitus status. The cohorts included 7560 and 30 258 patients for CABG and PCI, respectively. Following PCI, overall mortality was lower in patients with overweight and obese class I compared to those with normal BMI; however, 5‐ and 10‐year mortality rates were significantly higher in patients with obese class III with high‐risk coronary anatomy, which was primarily driven by higher mortality rates in patients without diabetes mellitus (5‐year adjusted hazard ratio, 1.78 [95% CI, 1.11–2.85] and 10‐year adjusted hazard ratio, 1.57 [95% CI, 1.02–2.43]). Following CABG, overweight was associated with lower mortality risks compared with normal BMI. Conclusions: Overweight was associated with lower mortality following CABG and PCI. Greater long‐term mortality in patients with obese class III following PCI, especially in those with high‐risk coronary anatomy without diabetes mellitus, warrants further investigation.